Clarifying and expanding the theory typology : A reply to readers’ comments - Sandberg, Jörgen; Alvesson, Mats (Marketing Theory, 2021)
We all want to develop impactful and valuable theories, but what do we mean by ‘theory’? In this piece, we reply to the four readers’ comments on a recent paper in which we propose a theory typology that, in comparison to existing literature, offers a considerably broader, more pluralistic and, at the same time, more precise definition of the meaning(s) of ‘theory’ within academia. In their comments, the readers raise several insightful points that encourage us to further clarify the theory typology, as well as to expand on how it can be useful for researchers in marketing and social science more broadly.
Keywords: Knowledge development; theoretical contribution; theorizing; theory; theory development